2019
DOI: 10.3390/w11040682
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the 21st Century Challenges in the Food-Energy-Water Security in the Middle East

Abstract: Developing countries have experienced significant challenges in meeting their needs for food, energy, and water security. This paper presents a country-level review of the current issues associated with Food-Energy-Water (FEW) security in the Middle East. In this study, sixteen countries in the Middle East are studied, namely Iraq, Iran, Syria, Lebanon, Israel, Palestine, Egypt, Turkey, and the Arabian Peninsula (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia (KSA), United Arab Emirates (UAE), and Yemen). Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 64 publications
1
38
0
1
Order By: Relevance
“…External (exogenous) drivers can simultaneously affect their behavior; thus, they need to be considered to address resilience challenges in terms of opportunities and trade-offs. External drivers can include climate variables and related extreme events-that is, temperature, precipitation, and drought-and socioeconomic stresses such as economic growth, population growth, poverty, political stability (Hameed et al, 2019). They can directly be linked in the FEW-WISE framework through multiple interactions and feedbacks across spatial and temporal scales (Chenoweth et al, 2011;King and Jaafar, 2015;Scanlon et al, 2017), thus creating risks and management challenges.…”
Section: Nm Few Nexus Driversmentioning
confidence: 99%
“…External (exogenous) drivers can simultaneously affect their behavior; thus, they need to be considered to address resilience challenges in terms of opportunities and trade-offs. External drivers can include climate variables and related extreme events-that is, temperature, precipitation, and drought-and socioeconomic stresses such as economic growth, population growth, poverty, political stability (Hameed et al, 2019). They can directly be linked in the FEW-WISE framework through multiple interactions and feedbacks across spatial and temporal scales (Chenoweth et al, 2011;King and Jaafar, 2015;Scanlon et al, 2017), thus creating risks and management challenges.…”
Section: Nm Few Nexus Driversmentioning
confidence: 99%
“…Hameed, et al [9] reviewed the 21 st century challenges that face food, energy and water (FEW) security in the Middle East. The study found that, most of the studied countries are facing FEW resource insecurities.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…These efforts brought some progress in reducing the overexploitation of water resources, enabled to increase the nonconventional water sources. Some wealthiest countries managed to create efficient systems of seawater desalinization to improve their irrigation infrastructure and drainage networks [69]. Based on MODIS data Badreldin and Goossens detected anti-desertification change in El-Tina plain and Qanatra Shark in Egipt in the studied years 2002, 2005, 2008 and 2011 and indicated that societal drivers contributed to mitigate and compact desertification process [70].…”
Section: Introductionmentioning
confidence: 99%